「銜接」課程統整的理論與實踐：以臺灣九年一貫改革下的教師觀點為例 - 歐用生Yung-Sheng Ou; 黃騰Teng Huang (Higher Education Foundation, 2007)
課程理論和實踐往往產生落差，這是課程改革上的一大困境。臺灣許多研究都試著去分析社會統整課程理論與實踐產生落差的原因，不過在這些研究當中，「教師」的觀點似乎都不是其主要關心的對象，很少研究是以「教師」的實踐現場做為研究的基礎，很少從「教師」觀點探討統整課程理論和實踐間的落差。 在理性主義的課程理論中，「教師」扮演「執行者」的「角色」，其工作目的就是要完成國家課程改革所要求的任務。在這樣的情況下，「教師」不需思考理論的精神與內涵，只需技術上的完成任務，結果導致「理論」與「實踐」的疏離。若要教師將「課程統整」的「理論」與現場的「實踐」結合，落實到班級的教學過程中，一定要覺醒教師的「道德意義」，讓他們尋求課程理論和實踐的「銜接」。本研究利用臺灣山水中學（化名）社會統整課程實施的經驗來探討這些問題。 Grade 1-9 curriculum reform has been implementating for 6 years in Taiwan, and Curriculum Intergration is the core project of the reform. The research originally hoped that we can have some "dialectics" between Curriculum Intergration theory and practice after we know the perspective of teacher. But after the research started, we found that teachers in school that never have the spirit of Curriculum Intergration in mind while they implementated. Therefore, we found the "dialectics" between Curriculum Intergration theory and practice in really difficult. Then we turned to think why there is a big gap between theory and practice, and how we can connect this gap. From the perspective of teacher, we find that "professional identity" is a very important fact and it involves deep reflexivity on moral meaning. Therefore, we think that the deep reflexivity on moral meaning could be the first step to connect Curriculum Intergration theory and practice.